2019
DOI: 10.3138/cpp.2019-016
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Canada Workers Benefit to Design a Guaranteed Basic Income

Abstract: We design a hybrid guaranteed basic income and earnings subsidy for working-age Canadians that addresses federalism and work disincentive concerns associated with a conventional basic income by expanding the Canada Workers Benefit. We cost our program and propose a revenue-neutral financing model by consolidating provincial SA programs and eliminating several federal and provincial tax credits. We simulate the distributional effects of our program and financing on household disposable income across deciles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…One type of supplementary social assistance offered in many high-income countries is in the form of refundable (or payable) tax credits, which provide cash benefits to eligible people with low incomes who file income tax returns. However, this form of income supplement has been criticized as being insufficient, especially for people with low incomes and without children (Koebel & Pohler, 2019). In the United Kingdom, only two types of refundable tax credits are currently offered: a working tax credit and a child tax credit (UK Government, 2022), so unemployed people without dependent children are not eligible for either.…”
Section: Policies and Programs For Reducing Povertymentioning
confidence: 99%
“…One type of supplementary social assistance offered in many high-income countries is in the form of refundable (or payable) tax credits, which provide cash benefits to eligible people with low incomes who file income tax returns. However, this form of income supplement has been criticized as being insufficient, especially for people with low incomes and without children (Koebel & Pohler, 2019). In the United Kingdom, only two types of refundable tax credits are currently offered: a working tax credit and a child tax credit (UK Government, 2022), so unemployed people without dependent children are not eligible for either.…”
Section: Policies and Programs For Reducing Povertymentioning
confidence: 99%
“…Whether the voice objective is balanced alongside efficiency and equity objectives in an income support program is determined by the extent to which it provides workers with a realistic fall-back option to losing a job, because this enables them to express concerns, for instance, about personal protective equipment in their workplace during the pandemic. Research has shown that legislated employment rights (e.g., to refuse unsafe work) are unfortunately not always enough to ensure protection for workers, particularly in non-unionized workplaces ( Lewchuk 2013 ; Pohler and Riddell 2019 ; Reilly, Paci, and Holl 1995 ; Walters 1996 ; Weil 1999 ). Knowing that you may not be eligible for income replacement or support benefits if you are terminated from your job might also prevent you from airing such grievances to your employer or to a Ministry of Labour official.…”
Section: Analytical Framework For Evaluating Covid-19 Crisis Policies...mentioning
confidence: 99%
“…What options do workers have if their employer does not address their concerns, if they are at higher risk of COVID-19 mortality, or if they are unable to perform their job from home? In non-union settings, the answer is “not many” (see, e.g., Pohler and Riddell 2019 ; Weil 1999 ). Thus, crisis income support programs should also be evaluated on how they affect the ability of workers (particularly low-income workers) to express (voice) concerns about workplace safety and their own risk preferences.…”
Section: Analytical Framework For Evaluating Covid-19 Crisis Policies...mentioning
confidence: 99%
See 2 more Smart Citations